(untitled) (Thành phố Hồ Chí Minh, 1996)
Built in 1929 by the Société des Études Indochinoises, this notable Sino-French museum houses a rewarding collection of artefacts illustrating the evolution of the cultures of Vietnam, from the Bronze Age Dong Son civilisation (which emerged in 2000 BC) and the Funan civilisation (1st to 6th centuries AD), to the Cham, Khmer and Vietnamese. The museum is just inside the main gate to the city’s botanic gardens and zoo.
Keywords: Museums,Museums,Bảo tàng,Bảo tàng; History,Lịch sử; Vietnam,Việt Nam